2011
DOI: 10.1501/vetfak_0000002462
|View full text |Cite
|
Sign up to set email alerts
|

mtDNA diversity and phylogeography of some Turkish native goat breeds

Abstract: Summary:Mitochondrial DNA is one of the most preferred markers being used in phylogenetic studies in domestic animals due to its unique features. In this study, the mitochondrial DNA control region was analyzed in Angora, Honamli, Kilis, Hair and Norduz goat breeds (n=252) to reveal diversity of mitochondrial DNA, differentiation of goat breeds, and relevance between genetic differentiations and geographic distributions. Based on the performed analysis methods, three different haplogroups; A, D and G were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…It has been suggested that the Kilis goat has been developed by crossing Anatolian Black goats with Damascus goats and by subsequent interbreeding among the cross‐bred generations (Yalcin ). In this study, no shared haplotypes between Kilis and Anatolian Black breeds were observed, which is consistent with the results of Kul and Ertugrul (), but the highest migration rates were observed between Anatolian Black and Kilis breeds.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It has been suggested that the Kilis goat has been developed by crossing Anatolian Black goats with Damascus goats and by subsequent interbreeding among the cross‐bred generations (Yalcin ). In this study, no shared haplotypes between Kilis and Anatolian Black breeds were observed, which is consistent with the results of Kul and Ertugrul (), but the highest migration rates were observed between Anatolian Black and Kilis breeds.…”
Section: Discussionsupporting
confidence: 92%
“…() used only 66 individuals from Turkey. In a recent study, Kul and Ertugrul () collected a total of 252 samples from five Anatolian breeds. In the previous studies, only haplogroups A, D and G were found in Anatolian goat breeds (Luikart et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last few years, considerable effort has been devoted to characterizing the genetic diversity of African, Asian, and European goats (e.g., Azor et al, 2005;Pereira et al, 2005;Cañón et al, 2006;Naderi et al, 2007;Çinar Kul and Ertuğrul, 2011), but locally adapted Latin American breeds have received much less attention. In Brazil, a few studies have recently addressed the existence of local breeds using either microsatellites or mtDNA, and all have focused on those from the northern region of the country, for example the Canindé, Graúna, Marota, Moxotó, Repartida, and Serrana Azul (Araújo et al, 2006;Menezes et al, 2006;Oliveira et al, 2007Oliveira et al, , 2010.…”
Section: Crespa As a Distinct Genetic Clustermentioning
confidence: 99%
“…Three wild species, bezoar (Capra aegagrus), markhor (C. falconeri) and ibex goats (C. ibex), have been considered as ancestors of domestic goats (C. hircus) (Harris 1962;Takada et al 1997;Wang et al 2008). Archaeological evidence and mitochondrial DNA (mtDNA) studies now indicate the bezoar from southeastern Turkey, northern Iraq and north-west Iran as the ancestor population (Luikart et al 2001;Naderi et al 2008;Pereira et al 2009;Cinar Kul & Ertugrul 2011;Zeder 2011). Arbuckle et al (2014) hypothesized that genotype and phenotype of early domestic goat populations were subject to interactions between ecogeographic conditions, cultural preferences, domestic animals and wild populations and changed already before the westward expansion from southeastern Turkey to Europe.…”
Section: Introductionmentioning
confidence: 99%